Managing Demurrrage Using Fmea (Failure Mode And Effect Analysis) – A Case Study Of Coal Mining Corporation In Indonesia - Sari, Dian Purnama (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
PT CMC (Coal Mining Corporation) is an Indonesian coal mining company that plays a role in meeting both domestic and export energy demands. At present, loading and unloading schedules for ships frequently overlap due to prolonged vessel scheduling, leading to increased demurrage costs. The arrival of multiple vessels at the same time often results in congestion, queues, and delays in loading and unloading operations. This situation not only escalates demurrage expenses but also undermines port operational efficiency and raises operational risks. To address these business challenges, this study aims to identify operational risks and propose effective improvement strategies to minimize demurrage. The research adopts a gap analysis approach integrated with Failure Mode and Effect Analysis (FMEA). A questionnaire was designed based on FMEA principles to assess severity, occurrence, and detection levels. Data were collected from 15 respondents, consisting of three distribution team members, seven from the Palembang dock team, and five from the transportation handling team. The findings, derived from a root cause investigation using the 5 Whys method, reveal 25 underlying causes of the problem. Based on the Risk Priority Number (RPN), the controllable risks in order of priority are: (1) waiting for cargo barges due to their unavailability, (2) simultaneous ship arrivals (overlapping schedules), (3) floating crane unavailability as it is still servicing another vessel, (4) queuing caused by prioritizing domestic vessels for loading, and (5) failure to meet the target loading rate. Recommended actions include: prioritizing high-impact issues by focusing first on the most critical problems, particularly barge resource allocation; implementing solutions systematically across all relevant operational areas; fostering cross-functional collaboration between the distribution, Palembang pier, and transportation handling teams to ensure integrated execution; adopting a phased strategy for short-, medium-, and long-term implementation; and establishing continuous performance monitoring.